Dampak Instruksi Physical Distancing dari Pemerintah dalam Mencegah Penyebaran Virus Corona pada Pembelajaran Jarak Jauh (PJJ) Peserta Didik MI/SD di Indonesia - eliza zalsabila; Anis Fuadah Z. (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
Health in life is very important. In dressing, food, and all activities in life must be carried out cleanly to maintain good health for ourselves and the environment. At the end of 2019 unrest arises in all corners of the earth due to the emergence of a new type of virus, the corona / covid-19 virus. Corona virus is a large family of viruses that attack the respiratory syndrome system. Viruses that have never been identified in humans before, according to WHO (World Health Organization) corona virus is zoonosis, which means transmitted between animals and humans. In this journal the title of the Impact of Physical Distance Instructions from the Government in Preventing the Corona Virus Spread on the Distance Learning of MI / SD Students in Indonesia. By raising the title aims to provide education to the general public in the face, prevent, and continue to live in a situation of unrest such as this. The journal is written in a descriptive form and also uses the literature method that is relevant to the title of the journal being raised. Keywords: Corona Virus, Prevention, Distance Learning